Respuesta :
We can use the elimination method to add the two equations together. Multiply the bottom equation by -1 to eliminate the x variable.
Equation 1: 3x + y= 9
Equation 2: 3x - 5y= 15
STEP 1:
Multiply equation 2 by -1
-1(3x - 5y= 15)
-3x + 5y= -45
STEP 2:
Add the two equations:
3x + y= 9
-3x + 5y= -45
the x variable is eliminated
6y= -36
divide both sides by 6
y= -6
STEP 3:
substitute y=-6 in either equation to solve for x
3x + y= 9
3x + (-6)= 9
3x - 6= 9
3x= 15
x= 5
CHECK:
3x + y= 9
3(5) + (-6)= 9
15 - 6= 9
9= 9
ANSWER: x= 5 and y= -6
Hope this helps! :)
Equation 1: 3x + y= 9
Equation 2: 3x - 5y= 15
STEP 1:
Multiply equation 2 by -1
-1(3x - 5y= 15)
-3x + 5y= -45
STEP 2:
Add the two equations:
3x + y= 9
-3x + 5y= -45
the x variable is eliminated
6y= -36
divide both sides by 6
y= -6
STEP 3:
substitute y=-6 in either equation to solve for x
3x + y= 9
3x + (-6)= 9
3x - 6= 9
3x= 15
x= 5
CHECK:
3x + y= 9
3(5) + (-6)= 9
15 - 6= 9
9= 9
ANSWER: x= 5 and y= -6
Hope this helps! :)
its -15 instead of -45
y=-1
x= 10/3
Equation 1: 3x + y = 9
Equation 2: 3x - 5y = 15
Multiply -1 to equation 2 to cancel out x
-1(3x -5y = 15)
-3x + 5y = -15
Cancel out x
3x + y = 9
-3x + 5y = -15
6y = -6
y = -1
Substitute y with -1 to solve x
3x + (-1) = 9
3x - 1 = 9
+1 = +1
3x = 10
3x/3 = 10/3
x = 10/3